Fadrique Alvarez de Toledo, 2nd Duke of Alba, and his Book Inventory (1531): a Patrimonial Library - Bustos Táuler, Álvaro; Sanmartín Bastida, Rebeca (Revista General de Información y Documentación, 2016)
Fadrique Álvarez de Toledo, 2nd Duke of Alba, who was born in 1460 and died in 1531, led in Castile the lineage of the House of Alba in the transition from the Middle Ages to the Renaissance. He was cousin of Ferdinand the Catholic and close associate of the Kings, and in addition to these relations he developed considerable patronage of arts and literature: among the best-known examples we count the support he offered to the poet and playwright Juan del Encina. In spite to these activities, he has not raised much interest from historians since his figure has been overshadowed by his grandson, the Grand Duke of Alba. This article presents the inventory of Don Fadrique’s library (the books that were catalogued after his death), unpublished until now and which displays a rich library that could be defined as patrimonial, with one hundred and eighty-six volumes. Among the religious books, in which we can count bibles, books of prayers and books of hours, we find some indispensable titles of the Dominican and Franciscan traditions, that portray a character engaged in the new devotional trend appeared at the end of the 15th century, in combination with an interest for Scholasticism (specially Saint Thomas Aquinas), and for medieval visionary and saintly women.